1996
DOI: 10.1016/0014-5793(96)00987-8
|View full text |Cite
|
Sign up to set email alerts
|

The untranslated first exon ‘exon OS’ of the rat estrogen receptor (ER) gene

Abstract: Recently, we have isolated the untranslated first exon 'exon ON' of the rat estrogen receptor (ER) gene from the liver by the use of the 5'-rapid amplification of cDNA ends (5'-RACE) method. To investigate the existence of other untranslated first exon(s), we further analyzed the 5'-untranslated region (UTR) of ER mRNA in the rat liver in this study. Total RNA from the livers of 8-week-old male Wistar rats was subjected to 5'-RACE with the antisense primers located in exon 1 of the rat ER gene. The inserts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 14 publications
(27 reference statements)
0
21
0
Order By: Relevance
“…These regions act as molecular switches that activate or deactivate transcription initiation through differential methylation mechanisms (Sasaki et al 2003, Champagne et al 2006. In the rat, it has been described that a system of untranslated first exons is associated with the promoter selection for ERa transcription initiation, and to date five active promoters called OS, ON, O, OT, and E1 (Koike et al 1987, Hirata et al 1996a,b, Donaghue et al 1999, Osada et al 2001) have been identified. Little is known about the precise function of each ERa promoter; however, it has been reported that a mechanism of promoter selection is involved in the complex stage-and region-specific regulation of ERa gene expression in many organs, including the rat brain (Kato et al 1998, Hamada et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…These regions act as molecular switches that activate or deactivate transcription initiation through differential methylation mechanisms (Sasaki et al 2003, Champagne et al 2006. In the rat, it has been described that a system of untranslated first exons is associated with the promoter selection for ERa transcription initiation, and to date five active promoters called OS, ON, O, OT, and E1 (Koike et al 1987, Hirata et al 1996a,b, Donaghue et al 1999, Osada et al 2001) have been identified. Little is known about the precise function of each ERa promoter; however, it has been reported that a mechanism of promoter selection is involved in the complex stage-and region-specific regulation of ERa gene expression in many organs, including the rat brain (Kato et al 1998, Hamada et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…A system of untranslated exons and regulatory elements determine ERα transcription initiation [56,57,58]. Estrogens are known to regulate the selective usage of these promoter systems [59] and although it has not been explicitly tested, sex differences in ERα promoter methylation may be related to alternative promoter selection and thereby involved in sexual differentiation of the brain.…”
Section: Sex-specific Dna Methylation During Development and Beyondmentioning
confidence: 99%
“…Six hER␣ messenger RNA (mRNA) isoforms (A-F hER␣ mRNAs) are generated by the alternative splicing of five upstream exons (1B-1F) to a common site upstream of the translation start codon (12a). Similarly, at least three ER␣ mRNA forms have been identified in the rat (13)(14)(15). These data suggest that alternative 5Ј-splicing and promoter usage is probably a general feature of the ER␣ genes in mammals.…”
mentioning
confidence: 71%